Procesos de aculturación coadyuvantes a la pérdida de identidad en la comunidad shuar del sitio Balao Chico. - Echeverria Martinez, Raisa Lizbeth (2018)
The Universal Declaration of Cultural Diversity by UNESCO and the legal regulations promulgated in Ecuador aimed at preserving the cultural heritage and socio-cultural identity of the people of aboriginal communities, establishes the obligatory nature of some research planning institutions and intervention in order to meet the social demands of specific aboriginal groups. One of these institutions is the university academy, which aims to develop the essential function of Linking with the Collective, which is like an articulating mechanism that enhances the other substantive functions of research and teaching, based on the diagnosis of social demands and planning of interventionist actions, thus achieving a better interaction and integration with their environment. The diversity of its career offer allows institutions of higher education through their teachers and students to meet multiple social requirements. The loss of cultural identity is currently affected due to the processes of acculturation that take place in our contemporary context, given by the widespread aberrant indiscrimination that is shown to certain social groups that value and care for their cultural identity, which leads them to adapt to new styles and ways of life to be able to socialize in the world and develop economically, socially and culturally.